Data as infrastructure? A study of data sharing legal regimes. Issue 2 (June 2020) - Ducuing, Charlotte
The article discusses the concept of infrastructure in the digital environment, through a study of three data sharing legal regimes: the Public Sector Information Directive (PSI Directive), the discussions on in-vehicle data governance and the freshly adopted data sharing legal regime in the Electricity Directive. While aiming to contribute to the scholarship on data governance, the article deliberately focuses on network industries. Characterised by the existence of physical infrastructure, they have a special relationship to digitisation and 'platformisation' and are exposed to specific risks. Adopting an explanatory methodology, the article exposes that these regimes are based on two close but different sources of inspiration, yet intertwined and left unclear. By targeting entities deemed 'monopolist' with regard to the data they create and hold, data sharing obligations are inspired from competition law and especially the essential facility doctrine. On the other hand, beneficiaries appear to include both operators in related markets needing data to conduct their business (except for the PSI Directive), and third parties at large to foster innovation. The latter rationale illustrates what is called here a purposive view of data as infrastructure. The underlying understanding of 'raw' data (management) as infrastructure for all to use may run counter the ability for the regulated entities to get a fair remuneration for 'their' data. Finally, the article pleads for more granularity when mandating data sharing obligations depending upon the purpose. Shifting away from a 'one-size-fits-all' solution, the regulation of data could also extend to the ensuing context-specific data governance regime, subject to further research.